Too Many Suspended Sentences? Polish or Central and Eastern European Problem? - Krajewski, Krzysztof (Sociologija. Mintis ir veiksmas, 2007)
This paper starts with an analysis of certain problems and issues regarding penal law and penal policies in Poland. However, it appears that these problems are not limited to Poland only. An analysis of comparative statistical data shows that they have a broader /European or, more precisely, a Central and Eastern European dimension. That is, they seem to be of a more general character and of significance in the context of a broader European discussion. Moreover, they may constitute a crucial component of the discussion on the approximation and unification of criminal law and penal policies in the European Union. Today, there are still substantial differences in this area not only between all the member states but particularly between the “old” and “new” members. Hence, there is a great need for considerable efforts to change and improve the existing situation.
Keywords: crime control policy; imprisonment; suspended sentences; “penal divide”